THE IMPACT OF STOCK EXCHANGE TURNOVER ON GDP IN THE REPUBLIC OF SERBIA - Malenković, Nebojša (Poslovna ekonomija, 2022)
Stock exchange turnover growth increases the capital performance within a country. This paper examines the stock exchange turnover trends after the global financial crisis while considering the novel COVID-19 global crisis in Republic of Serbia. Moreover, this paper estimates the correlation between the stock exchange turnover and GDP indicators. Since the COVID-19 crises is recent, the available official data for the last two years are not complete yet. Therefore, the aim of this research is to measure the impact of stock exchange turnover on economic growth in the Republic of Serbia for the period 2006-2020, with respective predictions. The methodological approach consist is the application of linear regression model, with previous statistical adequacy tests. The final results of this research indicate that the growth of stock exchange turnover has positive and statistically significant impact on GDP in this country. However, the prediction analysis indicates that the stock exchange turnover may have a negative impact on GDP in the next years, which is why there are several suggestions for decision makers and further research. Key words: stock exchange, BELEX, economic growth, correlation, regression, Serbia